Les firmes et la hausse des prix énergétiques - Gert Bijnens; Cédric Duprez (Banque Nationale de Belgique, 2022)
The sharp rise in energy prices affects all companies in all sectors of the economy. However, not all companies are in a comparable situation, as the share of energy in input purchases can vary from less than 1% to more than 50% from one industry to another. Most energy consumers are naturally more exposed. These include not only industry (basic chemical materials, pesticides, bricks, etc.), but also fishing, forestry, transport and data centres. To measure the impact of this shock on companies, the question is to know to what extent they can pass on the increase in their production costs to their selling prices. If they can do so, the shock is then passed on to the end consumers, whether households or foreign customers, who have to bear price increases. The historical and early current data available indicate some transmission capacity. We estimate that, on average, companies are able to pass on 60% of cost increases to their customers. This pass-through differs between industries and is more important for large companies than for small ones. For energy-intensive industries, the pass-through is generally higher than average, which should somewhat mitigate the effect of the energy shock on companies. However, since the transmission capacity is not complete, the margins of companies will decrease and absorb part of the shock. Under the effect of the indexation mechanisms, the rise in prices also has an impact on wages in Belgium. The labour-intensive branches of activity, mainly in services, are in turn affected. In general, labour-intensive sectors have a low energy intensity, and vice versa. This implies that few sectors experience both a large energy shock and a large wage shock. However, the magnitude of the combined shock is historical for some industries. In general, corporate margins have increased in 2021. A likely difficult year would therefore follow a good year. Here again, there are sectoral disparities, and some industries whose situation was already fragile in 2021 are under even greater pressure (air and inland waterway transport, fruit and vegetables, construction support).
Keywords: 330